EVALUASI KUALITAS LAYANAN DAN KEPUASAN PENGGUNA INFORMASI E-GOVERNMENT (WEBSITE) PADA SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KABUPATEN KOLAKA - Zaitun Zaitun; Ageng Setiawan Herianto; Budi Guntoro (Universitas Muhammadiyah Sidoarjo, 2013)
This research aimed to investigate the users’ satisfaction on information service e-government (website) service at Regional information management system (SIMDA) in Kolaka Regency. The methods used were qualitative and quantitative approaches. Qualitative approach used for process information management understanding by BAPESIKOM/PDE. Meanwhile, quantitative approach used to investigate the user satisfied on information service website based on the information management performance. The informants were interviewed in qualitative approach were 6 persons. The sample of users information service which chosen by simple random sampling method were 40 respondents. The result of the research shown that the information management was not qualified. It was presumed on no strategies to produce good quality of qualified information. Information service users of Kolaka Regional Regency stated their unsatisfied on the using of information service based Website.